Analysis of genetic and clinical characteristics of a Chinese Kallmann syndrome cohort with ANOS1 mutations. Issue 4 (October 2017) - Nie, Min; Xu, Hongli; Chen, Rongrong; Mao, Jiangfeng; Wang, Xi; Xiong, Shuyu; Zheng, Junjie; Yu, Bingqing; Cui, Mingxuan; Ma, Wanlu; Huang, Qibin; Zhang, Hongbing; et al.
Abstract : Objective: To analyze ANOS1 gene mutations in a large Chinese Kallmann syndrome (KS) cohort and to characterize the clinical presentation of the disease in patients with ANOS1 mutations. Patients and methods: Chinese patients with KS, including 187 sporadic and 23 pedigree cases were recruited. Patients' ANOS1 gene sequences were analyzed by direct sequencing of PCR-amplified products. In silico analysis was used to assess functional relevance of newly identified missense mutations. Patients' clinical characteristics were analyzed retrospectively. Result(s): Fifteen nonsynonymous rare ANOS1 variants were found in 13 out of 187 sporadic and 8 out of 23 familial IHH probands. Seven novel (C86F, C90Y, C151W, Y379X, c.1062 + 1G > A, Y579L fs 591X, R597X) and eight recurrent ANOS1 mutations (S38X, R257X, R262X, R423X, R424X, V560I, c.1843-1G > A, p.R631X) were identified. All the novel mutations were predicted to be pathogenic. The prevalence of cryptorchidism was high (38.1%) and occurred in patients with different kind of ANOS1 mutations, while the patients with the same mutation did not present with cryptorchidism uniformly. Conclusion(s): The prevalence of ANOS1 gene mutations is low in sporadic KS patients, but is much higher in familial KS patients. In the present study, we identify seven novel ANOS1 mutations, including two mutations in the CR domain, which are probably pathogenic. These mutations expand the ANOS1 mutation spectrum and provide a foundation for prenatal diagnosis and genetic counseling.